Parity in relation to the Compliance of Pregnant Mothers Attending a Pregnant Women’s Class in the Working Area of the Health Center of Bandung Tulungagung District - Retnaningtyas, Erma; Siwi, Retno Palupi Yonni; Wulandari, Anggrawati (International Journal of Psychosocial Rehabilitation, 2020)
The parity of pregnant women means that some pregnant women have experience in undergoing pregnancy and childbirth, making them no longer routinely attend class activities. The study objective was to find out the relationship between parity and the adherence of pregnant women when taking classes in the Working Area of Bandung District Health Center, Tulungagung. The design used was correlational and analytical with a prospective approach. The population consisted of 30 pregnant women in Sukoharjo Village, Soko Village and Singgit Village. The sample was taken through total sampling. The independent variable was parity and the dependent variable was the compliance of the pregnant mother to follow the pregnant women’s class. The data was collected using a questionnaire and observation sheet before being analyzed using a Chi square test with a p value < 0.05. The results showed that most were multiparous mothers (63.4%) and that 80% of them have a routine involving attending the classes. The results how there to be a relationship between parity and the compliance of the pregnant mothers to attend the pregnant women’s class (p= 0.017). Parity can affect the compliance of pregnant women when it comes to attending the classes for pregnant women. The most common result for parity was multipara parity. Parity relates to having experience and information related to undergoing pregnancy and childbirth.